Human macrophage polarization determines bacterial persistence of Staphylococcus aureus in a liver-on-chip-based infection model. (August 2022) - Siwczak, Fatina; Cseresnyes, Zoltan; Hassan, Mohamed I.Abdelwahab; Aina, Kehinde Oluwasegun; Carlstedt, Swen; Sigmund, Anke; Groger, Marko; Surewaard, Bas G.J.; Werz, Oliver; Figge, Marc Thilo; Tuchscherr, Lorena; Loffler, Bettina; et al.
Abstract: Infections with Staphylococcus aureus ( S. aureus ) have been reported from various organs ranging from asymptomatic colonization to severe infections and sepsis. Although considered an extracellular pathogen, S. aureus can invade and persist in professional phagocytes such as monocytes and macrophages. Its capability to persist and manipulate macrophages is considered a critical step to evade host antimicrobial reactions. We leveraged a recently established human liver-on-chip model to demonstrate that S. aureus specifically targets macrophages as essential niche facilitating bacterial persistence and phenotype switching to small colony variants (SCVs). In vitro, M2 polarization was found to favor SCV-formation and was associated with increased intracellular bacterial loads in macrophages, increased cell death, and impaired recruitment of circulating monocytes to sites of infection. These findings expand the knowledge about macrophage activation in the liver and its impact on bacterial persistence and dissemination in the course of infection.